## Tuesday, October 18, 2016

### Optimizing complex generator expressions [Updated]

The core expression is similar to this

y = (f(x) for x in L if f(x) is not None)

There are a lot of variations on the filter. The point is that the function appears twice in the above expression.

We have a number of alternatives.

• y = filter(None, f(x) for x in L)
• y = filter(None, map(f, L))
• y = (x for x in map(f, L) if x)
• y = (x for x in (f(y) for y in L) if x is not None)
• y = (val for x in L for val in (f(x),) if val is not None)

My preference is two steps, even though I don't really have a good reason for this.

y1 = (f(x) for x in L)
y2 = (f for f in y1 if f)

The thread leads to this path: https://twitter.com/TomAugspurger/status/786922167522828289  and the idea of "Let Bindings." We could extend the language slightly to bind a variable within the confines of the generator expression.

Like this:

y = (f(x) as val for x in L if val is not None)

The as clause binds the f(x) to val so that it can be used in the if clause.

Summary: Interesting.